Peripartum Phenomenon in Crioula Lanada Sheep Susceptible and Resistant to Gastrointestinal Nematodes - Pereira, Fabiellen Cristina; Longo, Cibele; Castilho, Caliê; Leme, Denise Pereira; Seugling, Jaqueline; Bassetto, César Cristiano [UNESP]; Amarante, Alessandro F. T. [UNESP]; Bricarello, Patrizia Ana (Frontiers, 2020)
This study aimed at evaluating parasitological and blood variables in native breed Crioula Lanada sheep belonging to the same herd, to identify and compare susceptible or resistant individuals to gastrointestinal nematodes during gestation and lactation phases. For this purpose, 18 Crioula sheep were used within 2 years of evaluation, in which blood and feces samples and weight of the animals were taken from their 4th month of gestation until the weaning of their lambs, in the 4th month postpartum. Feces samples were used for counting eggs per gram of feces (EPG) and, thus, to identify 12 resistant ewes (EPG < 1,000) and 6 susceptible (EPG > 1,000) to gastrointestinal nematodes. The identification of infective larvae was also performed. Blood was used for analysis of packed cell volume (PCV), eosinophil count, total plasma protein, and immunoglobulin G level against Haemonchus contortus infective larvae. The Kruskal–Wallis non-parametric comparison test was used to evaluate the differences between days of parturition and linear mixed-effects model using package lme4 in R to evaluate the groups. The main parasite species observed in the feces samples were Haemonchus, Trichostrongylus, Oesophagostomum, Ostertagia, and Cooperia in similar proportions in both groups. Susceptible ewes presented peaks of EPG at the beginning of lactation and lower PCV values throughout the study. No difference between groups was observed concerning other blood variables or body weight, but some changes were observed along with the gestation and lactation phases within each group. The physiological response of sheep to nematode infection is a useful tool to identify the most susceptible individuals within the same breed and herd and to select the most genetically resistant individuals.
Keywords: blood parameters; breed; ewes; immune response; parasitology; sheep-nematoda